2007
DOI: 10.1103/physrevlett.99.147008
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Competing Order in a High-TcSuperconductor Using Femtosecond Optical Pulses

Abstract: We present studies of the photoexcited quasiparticle dynamics in Tl2Ba2Ca2Cu3Oy (Tl-2223) using femtosecond optical techniques. Deep into the superconducting state (below 40 K), a dramatic change occurs in the temporal dynamics associated with photoexcited quasiparticles rejoining the condensate. This is suggestive of entry into a coexistence phase which, as our analysis reveals, opens a gap in the density of states (in addition to the superconducting gap), and furthermore, competes with superconductivity resu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 28 publications
3
46
0
Order By: Relevance
“…9,11,25,26 This fundamental discrepancy was attributed to the dependence of ΔR/R on several factors including laser power, 15,23 wavelength, 25,27 polarization, 25,28 and repetition rate 24,29 . Furthermore, in a recent effort to uncover the transient optical signatures of the pseudogap (PG) phase, [11][12][13][14]28,[30][31][32] and elucidate a possible relationship between the PG state and SC state in OD YBCO [31][32] , the PG phase was either identified as a weak transient feature 11,30 or found to be completely absent from the spectra. 9,19,25,26 Here, we report on a new procedure to obtain the definitive ultrafast optical RT model.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9,11,25,26 This fundamental discrepancy was attributed to the dependence of ΔR/R on several factors including laser power, 15,23 wavelength, 25,27 polarization, 25,28 and repetition rate 24,29 . Furthermore, in a recent effort to uncover the transient optical signatures of the pseudogap (PG) phase, [11][12][13][14]28,[30][31][32] and elucidate a possible relationship between the PG state and SC state in OD YBCO [31][32] , the PG phase was either identified as a weak transient feature 11,30 or found to be completely absent from the spectra. 9,19,25,26 Here, we report on a new procedure to obtain the definitive ultrafast optical RT model.…”
mentioning
confidence: 99%
“…[1][2] Time-resolved spectroscopy with ultrafast temporal resolution is a complementary tool to investigate the temporal evolution of the QP-bosonic degrees of freedom [3][4][5][6][7][8] that is capable to disentangle the contribution of bosonic excitations from the dynamics viewpoint. 6 Based on this observation, the non-equilibrium optical spectroscopy has been extensively applied to explore mechanisms of phase separation, [9][10][11][12][13][14][15] boson pairing, 16 and the electron-phonon coupling [17][18][19][20][21] in superconductors by monitoring the QP dynamics; the experimental results are conventionally connected to microscopic processes by application of a phenomenological model proposed by Rothwarf and Taylor (i.e. the RT model).…”
mentioning
confidence: 99%
“…Usually the anomalous T dependence of τ exp is observed in many gapped systems, for example, phaseordered systems showing an energy gap opening in the electron band below the transition temperature T c . It has been found that a wide variety of superconductors [1][2][3][4][5][6][7][8][9][10][11][12][13] and density-wave compounds [14][15][16][17][18][19] show diverging behavior of τ exp near T c , as confirmed by femtosecond time-resolved optical spectroscopy. 1,4,5,[7][8][9][10][11][12][13][14][15][16][17]19 The divergence of τ exp in these gapped systems is believed to result from a recursive energy transfer between electrons and phonons.…”
Section: Introductionmentioning
confidence: 90%
“…(22) is of great importance. The formula is applicable to τ exp in other gapped systems such as Tl-based cuprate superconductors 2,6 and the solid fullerenes K 3 C 60 and Rb 3 C 60 (Ref. 3).…”
Section: B Comparison With Experimental Datamentioning
confidence: 99%
See 1 more Smart Citation